DECISION SUPPORT SYSTEM TO DETERMINE FUTURE PLANTING OF CLOVE IN SAMIGALUH KULON PROGO USE METHOD OF WEIGHTED PRODUCT (Dinamika Informatika, 2016)
Indonesian clove farmers especially located in Samigaluh, Kulon Progo, recentky still use traditional methods for determining period of planting as using Javanese calendar, early raining season. It is needed a decision support system to determine planting clove period based on its land characteristics, in order to produce cloves maximally. The study aims at developing a decision support system application to determine planting clove period by using weighted product method. Method of data collection used literature review,internet browsing and interview. Decision support system to determine the clove planting period was built with PHP programming language and MySQL database. The stage development application include analyzing. System designing, implementing, and testing. Application of decission support system by weighted product method can be used to determine the clove planting period in Samigaluh, Kulon Progo, so that people determine the planting period easier than before, and yield maximal clove product. The test result shows that this application is feasible and can be used as tool to determine next clove planting period. Keywords: Decision Support Systems, Weighted Product, Samigaluh Kulon Progo. Para petani cengkeh di Indonesia khususnya di Kecamatan Samigaluh Kabupaten Kulon Progo saat ini masih menggunakan metode tradisional secara turun temurun dalam menentukan masa tanam dari cengkeh, misalnya dengan menggunakan kalender Jawa, awal mulai turun hujan, dan sebagainya. Sehingga diperlukan sistem pendukung keputusan dalam menentukan masa tanam pohon cengkeh agar petani cengkeh dapat mengetahui kapan waktu yang tepat untuk menanam cengkeh berdasarkan karakteristik daerahnya, sehingga hasil dari pertanian cengkeh dapat  maksimal. Penelitian ini bertujuan untuk membangun suatu aplikasisistem pendukung keputusan dalam menentukan masa tanam pohon cengkeh menggunakan metode weighted product. Metode pengumpulan data dengan menggunakan metode studi pustaka,browsing internet, dan wawancara. Aplikasi sistem pendukung keputusandalam menentukan masa tanam pohon cengkeh dibangun dengan bahasa pemrograman PHP dan Database MySQL. Tahap pengembangan aplikasi meliputi analisis, perancangan sistem, implementasi, dan pengujian. Aplikasi sistem pendukung keputusandengan metode weighted product yang dibuat dapat digunakan untuk menentukan masa tanam pohon cengkeh di Samigaluh Kulon Progo, sehingga masyarakat menjadi lebih mudah dalam menentukan masa tanam pohon cengkeh dan hasil dari pertanian cengkeh dapat  maksimal.Hasil pengujian sistem menunjukkan bahwa aplikasi ini layak dan dapat digunakan sebagai alat untuk menentukan masa tanam pohon cengkeh.   Kata Kunci: Sistem Pendukung Keputusan, Weighted Product, Samigaluh Kulon  Progo